2018
DOI: 10.1109/tbme.2017.2757878
|View full text |Cite
|
Sign up to set email alerts
|

Low-to-High Cross-Frequency Coupling in the Electrical Rhythms as Biomarker for Hyperexcitable Neuroglial Networks of the Brain

Abstract: Publisher's Statement © 2017 IEEE. Personal use of this material is permitted.Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works. How to cite TSpace itemsAlways cite the published version, so the author(s) will receive recognition through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…It has been suggested that CFC is a key mechanism in maintaining the inhibitionexcitation interaction balance and facilitating cerebral information flow. 36,37 In the classical CFC theory, it has been proposed that pulse of inhibition paced at LFA and targeted at the generators of HFA [38][39][40] : when LFA paced inhibition starts to ramp down, the fastspiking interneurons would start firing. 36 However, CFC is an undirected metric and can only assess the coupling strength, so the directional communication between LFA and HFA is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that CFC is a key mechanism in maintaining the inhibitionexcitation interaction balance and facilitating cerebral information flow. 36,37 In the classical CFC theory, it has been proposed that pulse of inhibition paced at LFA and targeted at the generators of HFA [38][39][40] : when LFA paced inhibition starts to ramp down, the fastspiking interneurons would start firing. 36 However, CFC is an undirected metric and can only assess the coupling strength, so the directional communication between LFA and HFA is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…33 In epilepsy patients, elevated CFC had been found within SOZ during the ictal period but not the nonictal periods, 34,35 probably indicating a hyperexcitable ictal state. 36 However, CFC is an undirected metric and can only assess the coupling strength, so the directional communication between LFA and HFA is still unknown. Here, we utilized CFD 17 to investigate the directional interactions between LFA and HFA in the epileptic network with a specific focus on focal seizure evolution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations